ENGLISH TERMINOLOGY FOR TECHNICAL COMMUNICATION: ESSENTIAL SKILLS FOR MODERN ENGINEERS (E Global Congress, 2023)
This article discusses the importance of English terminology in technical communication for modern engineers. In today's globalized world, English has become the dominant language for technical communication and a lack of proficiency in technical English can result in decreased career opportunities and hindered professional success. This article provides an overview of essential English skills for engineers including vocabulary, grammar, and writing techniques. Additionally, the article offers strategies for improving these skills and resources for continued learning. Overall, this article emphasizes the importance of English proficiency in technical communication to achieve success in an increasingly diverse and global workforce.